Tourism seasonality and tax compliance of hotel and accommodation sector in Magelang Regency, Indonesia: Mediating role of intention to comply - Suci Nasehati Sunaningsih; Agustina Prativi Nugraheni; Alex Johanes Simamora; Budi Hartono; Mumpuni Wahyudiarti Sitoresmi (Journal of Accounting and Investment, 2024)
Research aims: This research examined the effect of hotel and accommodation performance during peak seasons on tax compliance, especially tourism seasonality-based financial performance, intention to comply, and tax compliance behavior. This research also examined the effect of tourism seasonality-based financial performance on tax compliance behavior through intention to comply.Design/Methodology/Approach: The research sample includes 48 owners and top managers of hotels and accommodations in Magelang Regency. Questionaries measure the variable. Data analysis used structural equation modeling, which included the inner model, outer model, and path analysis.Research findings: Based on data analysis, tourism seasonality affected tax compliance in the hotel and accommodation sector. The peak season of tourism brought more revenues and cash, so hotels and accommodations could pay the tax and comply with tax regulations. Intention to comply mediated the effect of tourism seasonality-based financial performance on tax compliance behavior.Theoretical contribution/Originality: This research provided new evidence of peak season on tax compliance. This research also extended the ability to pay theory of taxation based on tourism seasonality. This research also evaluated regulations of Local Regulation of Magelang Regency No. 13 2010 and Regulation of Head of Magelang Regency No. 44 2012 in tourism seasonality since no regulation regulates seasonal tax system based on tourism seasonality for hotels and accommodation.